Eucharistic Eating, Family Meals and the Health of Adolescent Girls. Issue 2 (1st June 2014) - Michaelson, Valerie; Trothen, Tracy J.; Davison, Colleen; Elgar, Frank J.; Pickett, William
Abstract This national study of adolescent Canadian girls focuses on church or religious group involvement as a potential determinant of health, as well as participation in family meals as a spiritual practice with potential health benefits. Current church involvement did not relate to improved emotional health, suggesting the need for more integrative messages and practices. Findings confirmed the strong protective relationship between regular participation in the family meal and health benefits among girls. Drawing on health research and theological reflection, we argue that regular participation in the family meal is a potentially powerful practice that could benefit adolescent girls. By helping families to understand the importance of the family meal as a spiritual practice, and by providing practical, theologically rich tools for practicing the family meal in our busy culture, these findings have the potential to contribute to the overall holistic health of young people, both in and outside the church.